Morphological and Yield Traits of Pole-Type French Bean Genotypes - Luitel, Binod Prasad; Kalauni, Santosh; Bhandari, Bishnu Bahadur (Journal of Nepal Agricultural Research Council, 2021)
Understanding the phenotypic variation and association between the grain yield, and other agronomic traits in French bean genotypes is important for its varietal improvement program. Field experiments were conducted during 2018 and 2019 cropping season at Horticulture Research Station, Dailekh, Karnali Province of Nepal to evaluate pole-type French bean genotypes for plant morphological characters, yield and the association between the agronomic traits. Twelve (Bhatte, Chaumase, Dhankute Chhirke, WP Con Bean, White OP, Dhundi Raj, LB-31, LB-37, LB-39, Madhav, Chinese Long, and Trishuli) pole-type French bean genotypes were laid out in a randomized complete block design (RCBD) with three replications. Pole-type French bean genotypes showed the significant variation for plant morphological traits and grain yield. Genotype LB-31 exhibited significantly the highest pod number (78.0/plant), green pod weight (675.0 g/plant), green pod yield (36.1 t/ha), and dry grain yield (2.4 t/ha). Following LB-31 genotype, genotype Chaumase and LB-39 produced the highest green pod yield (31.3 t/ha and 31.2 t/ha, respectively). The number of clusters per plant, pod number per plant and green pod weight per plant exhibited the significant positive correlation with green pod and dry grain yield. Hence, these traits can be selected to improve the yield potential of pole-type French bean genotypes. Pole type French bean genotypes used in the experiment were well adapted to the study area. Therefore, the high yielding genotypes viz LB-31, Chaumase and LB-39 could be recommended to use as seed source for on-farm production in Mid-Western Nepal.